NILAI PERUSAHAAN DI INDONESIA: PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, DAN RASIO KEUANGAN - Vick, Clorine; Tjhai, Fung Jin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to obtain empirical evidence on the effects of various independent variables on firm value, which is measured by price to book value (PBV). The object of this research includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for a three years period from 2021 to 2023. Purposive sampling was employed as the sampling method, and multiple regression analysis was used for data analysis. There were 42 companies and 126 data that met the research criteria. The results indicate that liquidity, profitability, institutional ownership, and leverage have positive effects on firm value. This also show that high liquidity contributes to financial stability and flexibility. Profitability shows asset management efficiency. Institutional ownership improves governance. High leverage signals the company’s confidence in future prospects. Meanwhile, company size, activity ratio, dividend policy, and sales growth have no effects on firm value.